Energy Balance and Runoff in the Eastern Arctic - Maidlow, J.L. (My University, 1979)
Extensive interest in the exploitation of the natural resources of the Canadian High Arctic has been generated by the petrochemical and mining industries. This, in conjunction with the recent rapid growth of many communities in the Arctic has resulted in the need for reliable sources of potable water. Basic data deficiencies in the Arctic however preclude the use of traditional techniques for predicting the temporal distribution of runoff or peak from rates.
An interactive computer program using a modified energy budget concept has been developed to permit the simulation of average daily discharges from small watersheds in the Baffin region. All available hydrometeorologic data are utilized by the model which is formatted in a manner to facilitate data manipulation. Sensitivity analyses can thus be carried out to determine the sensitivity of a watershed's response to various meterologic parameters.
Calibration and subsequent verification of the model against data collected from two watersheds in the Baffin region yielded a high correlation between recorded and simulated discharges.
Keywords: Civil Engineering; Civil Engineering